Economic Growth Model with Regional Expenditure as a Moderation Variable: Scale in Berau Regency - Roy, Juliansyah; Rochaida, Eny; Suharto, Rahcmad Budi (Yayasan Ilomata, 2024)
The motivation of this paper aims to investigate the relationship between local taxes, DAU, and DBH on the economic growth of Berau Regency. Apart from that, the paper also identifies the relationship between regional taxes, DAU, and DBH on economic growth which interacts with regional expenditure in Berau Regency. Government revenue is an important instrument for regions to foster economic growth. At the same time, government spending is used as a fiscal support to review the degree of budget absorption. With surplus revenue performance, it will generate financing which also plays a vital function in boosting economic growth. Secondary data for 2013–2022 was collected from government budget documents. Then, the data is tabulated using a time-series linear regression model with moderating variables. The statistical output finds that regional taxes and DBH have a negative effect on economic growth. However, DAU actually has a positive effect on economic growth. Uniquely, the interaction between regional taxes and DAU which is moderated by regional spending has a positive influence on economic growth. Then, regional spending plays a negative role in the relationship between DBH and economic growth. Future implications of considering practical regulations that do not only depend on income from the DAU side, but must focus on the existence of regional taxes in Berau Regency. By optimizing regional taxes, it also allows for a large fiscal gap in terms of regional spending. Financing the development of Berau Regency requires adequate expenditure allocation.